News articles as a platform for library resource endorsement and dispersion. Issue 1 (13th February 2018) - Kundu, Srijani; Mondal, Parikshit
Abstract : Purpose: This paper aims to make news as a platform for the libraries to transmit information from the library resources and events to the huge mass of the society. The focus of the study is to design a flowchart of digesting the daily news and interlink them regularly to the library resources and events to build up a chain of development on a topic, enhance the easy promotion of the library resources to the public and offer them easy access to information. Design/methodology/approach: The study is a theoretical explanation from the point of view of increasing the use of news acquired by a library and its resources. Literature on news-clipping service of the libraries, various news-clipping software and the trending online news applications have been studied extensively to ensure a harmonic design of the proposed flowchart. Findings: The findings of the study describe the news digests that are expected as the outcome of the flowchart. The significant features and advantages of the news digests have also been discussed in the study. Research limitations/implications: The limitation of the study is that the flowchart which has been designed and described in this study is a blueprint. It has not been developed in real and has not been tested. But from the library's perspective, if the flowchart is developed and implemented in each library, it will maximize the utilization and consumption of information from the news and library resources. Originality/value: News applications are dynamic and often publish similar or ambiguous news which is difficult for an individual to identify. Moreover, the libraries mostly provide news-clipping service. If the libraries can collect the news and process them in their own way, it can extract the complete and actual information. The libraries can also tag their possessions for complementing each news digest and thus providing the users for accessing an authentic content of information.